Liability For Illegal Trade in Protected Non-Endemic Wildlife in Indonesia - Aris Dwi Setyawan (Publikasi Indonesia, 2024)
One of the most important natural wealth for humans is the diversity of animals found on this earth. Every country on earth has its diversity of animals; some examples are the Komodo dragon from Komodo Island, Indonesia, the giant panda from Shaanxi Province, China, the wildebeest from the Serengeti, Tanzania, the grizzly bear from Alaska, United States, and synchronous fireflies from Selangor Malaysia. Along with the development of technology, it turns out that the internet has also become the dominant factor influencing the amount of trade in protected endangered species. So far, thousands of protected animals are sold regularly via the internet. Both sellers of protected animals and their buyers take advantage of the advantages of the internet, which cannot be found in the real world, namely anonymity and the wide reach of the capital market. According to the Head of the Ministry of Forest Protection and Nature Conservation, According to Law no. 5 of 1990 concerning the Conservation of Living Natural Resources and Their Ecosystems, Conservation of living natural resources is living natural resources which use them as needed to ensure compliance with their needs and improve the quality of the aid and its value. Conservation of living natural resources and ecosystems is based on preserving and utilising living natural resources and their ecosystems harmoniously and balanced.